Hybrid Educational Leadership Preparation: Enhancing Flexibility and Engagement with Technology. Issue 2 (19th August 2019) - Torres, Chris; Gilzene, Alounso
Abstract : The current article describes the potential advantages and challenges to a novel hybrid approach, which combines a fully online section with an in‐person class. First, the format afforded greater flexibility for students who are teaching or leading on a full‐time basis, some of whom need to drive long distances if they wish to attend our leadership program. Second, the format has the potential to create meaningful interaction between students in different teaching and learning contexts (e.g., suburban/urban/rural) and thus exposure to different contexts, experiences, and points of view. Third, instructors can experiment with new technological strategies to have in‐person students interact with online students around the same content in classroom activities. We conclude by pointing out that pilot approaches such as these must iteratively seek and respond to student feedback to optimize the chances of being successful.